2003
DOI: 10.1007/s00125-003-1232-3
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin C-peptide increases nitric oxide production by enhancing mitogen-activated protein-kinase-dependent transcription of endothelial nitric oxide synthase in aortic endothelial cells of Wistar rats

Abstract: Aims/hypothesis. Recent studies have suggested that proinsulin C-peptide improves vascular functions, possibly through nitric oxide (NO) production. To clarify the molecular mechanisms of vascular NO production induced by C-peptide, we examined the effects of C-peptide on NO production and NO synthase expression in rat aortic endothelial cells in connection with mitogen-activated protein kinase (MAPK) activation. Methods. Aortic endothelial cells were isolated from female Wistar rats, cultured to confluence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 37 publications
7
83
1
3
Order By: Relevance
“…It has been suggested that C-peptide plays an important role in the maintenance of vascular homeostasis via its effects on eNOS [8]. There is also evidence to indicate that C-peptide participates in the control of renal Na + , K + -ATPase activity, thereby contributing to the regulation of tubular sodium handling during postprandial periods [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that C-peptide plays an important role in the maintenance of vascular homeostasis via its effects on eNOS [8]. There is also evidence to indicate that C-peptide participates in the control of renal Na + , K + -ATPase activity, thereby contributing to the regulation of tubular sodium handling during postprandial periods [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that C-peptide binds to a G-protein-coupled membrane binding site on a number of different cell types [1], thereby triggering Ca 2+ -dependent intracellular signalling pathways [2] including the mitogen-activated protein (MAP) kinase cascade [3,4]. This results in subsequent activation of both Na + , K + -ATPase [5][6][7] and endothelial nitric oxide synthase (eNOS) [5][6][7][8]. Activation of these enzyme systems is of particular interest in diabetes, since both are reported to be deficient in this disorder [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying these beneficial effects of C-peptide is a partial restoration of the diabetesinduced reduction in Na Ļ© ,K Ļ© -ATPase activity of the nerves (13,14). Moreover, C-peptide is known to have a stimulatory effect on endothelial nitric oxide synthase (15,16), thereby augmenting endoneurial blood flow (7,17). C-peptide also exerts neurotrophic effects and has an inhibitory effect on cellular apoptosis (for review, see ref.…”
mentioning
confidence: 99%
“…Activation of the Na -K pump by C-peptide was also demonstrated in man (15), but whether the protection by C-peptide against diabetic complications is mediated by this mechanism remains unclear. Of interest, recent findings indicate that C-peptide increases calcium influx and stimulates endothelial nitric oxide synthase (16,17), possibly through the activation of the mitogen-activated protein (MAP) kinase (18).…”
Section: Introductionmentioning
confidence: 99%